Financial Incentive Reforms and Hospital Performance: A Systematic Review of Governance Mechanisms and Institutional Effects - Merlin Hatumena; Nyoman Sri Subawa; Ida Ayu Oka Martini; Made Suidarma (AIBPM Publisher, 2026)
Hospital payment reforms, including pay-for-performance (P4P), diagnosis-related groups (DRG), bundled payments, value-based purchasing, and hybrid incentive systems, have been widely implemented to improve hospital quality, efficiency, and accountability, although empirical findings remain inconsistent across healthcare settings. This study aims to synthesize and evaluate the effectiveness of financial incentive reforms on hospital-level performance outcomes and identify the contextual factors influencing their implementation. Using a systematic review approach based on the PRISMA 2020 guidelines, this study analyzed 28 hospital-level studies published in Scopus-indexed journals (Q1–Q3) between 2015 and 2026. The findings indicate that 67.9% of the reviewed studies reported positive associations between payment reforms and hospital performance, particularly in process-based quality indicators, readmission outcomes, and selected efficiency measures. However, the effects on mortality, equity, utilization, and cost efficiency remain heterogeneous and context-dependent. The effectiveness of reforms is influenced by incentive magnitude, payment model type, indicator specificity, regulatory environment, baseline institutional performance, and digital monitoring capacity. These findings suggest that financial incentives are more effective when integrated into coherent governance and accountability systems.